Biostimulant modulate the physiological and biochemical activities, improving agronomic characteristics of bell pepper plants under salt stress - André Lucas Januário Silva; Otília Ricardo de Farias; Élida Barbosa Corrêa; Claudivan Feitosa de Lacerda; Alberto Soares de Melo; Mônica Danielly de Mello Oliveira (Scientific Reports)
Abstract Salinity is a significant environmental stress impacting plant growth and metabolism in irrigated areas of arid and semi-arid regions; the use of biostimulants is an effective alternative to enhance plant productivity under saline conditions. This study examined the effects of salinity stress by applying various electrical conductivities (0.5, 1.5, 2.5, 3.5, and 4.5 dS m− 1) of irrigation water combined with foliar application of the in combination with foliar application of biostimulant VIUSID Agro (0, 0.3, and 0.6 mL L− 1) on the growth, productivity, physiological, and biochemical responses of bell pepper plants in a greenhouse. Conducted in a factorial design with a completely randomized layout and five replications, and the results indicated that salinity caused a significant reduction in growth, decreased chlorophyll levels, and increased malondialdehyde levels, osmoregulators, and antioxidant enzyme activity. Plants treated with biostimulant demonstrated relatively superior growth parameters, such as plant height, dry matter, leaf area and number of leaves, as well as fruit quality, such as fruit size, firmness, ascorbic acid and soluble solids. Both doses of the biostimulant effectively mitigated the effects of salt stress by maintaining higher chlorophyll levels (15% increase), enhancing photosynthetic performance (20% increase), and improving fruit size and quality, as well as leaf water status, ultimately leading to better crop performance. The biochemical mechanisms through which these effects occur include enhanced osmoregulation and increased antioxidant activity. The foliar application of the biostimulant was an effective strategy to enhance the tolerance of bell pepper plants under salt stress conditions and can serve as a sustainable solution for agricultural production in saline irrigation water.